Role of CAR T Cell Metabolism for Therapeutic Efficacy - Rial Saborido, Judit; Völkl, Simon; Aigner, Michael; Mackensen, Andreas; Mougiakakos, Dimitrios (Cancers, 2022)
Chimeric antigen receptor (CAR) T cells hold enormous potential. However, a substantial proportion of patients receiving CAR T cells will not reach long-term full remission. One of the causes lies in their premature exhaustion, which also includes a metabolic anergy of adoptively transferred CAR T cells. T cell phenotypes that have been shown to be particularly well suited for CAR T cell therapy display certain metabolic characteristics; whereas T-stem cell memory (TSCM) cells, characterized by self-renewal and persistence, preferentially meet their energetic demands through oxidative phosphorylation (OXPHOS), effector T cells (TEFF) rely on glycolysis to support their cytotoxic function. Various parameters of CAR T cell design and manufacture co-determine the metabolic profile of the final cell product. A co-stimulatory 4-1BB domain promotes OXPHOS and formation of central memory T cells (TCM), while T cells expressing CARs with CD28 domains predominantly utilize aerobic glycolysis and differentiate into effector memory T cells (TEM). Therefore, modification of CAR co-stimulation represents one of the many strategies currently being investigated for improving CAR T cells’ metabolic fitness and survivability within a hostile tumor microenvironment (TME). In this review, we will focus on the role of CAR T cell metabolism in therapeutic efficacy together with potential targets of intervention.
CRIS-Team Scopus Importer:2022-11-25
Keywords: bioenergetics; CAR T cells; immune escape; immunometabolism; metabolism; tumor microenvironment